Growing Presence of Real Options in Global Financial Markets. - Kensinger, John W. (Research in Finance, 2017)
The broad theme of this volume of Research in Finance is "Comparing the Influence upon Equity Valuation of Strategy Compared with Cash Flow Expectations." Contributions assess the strong role of strategy in equity valuation, compared with valuation of expected dividends.